2011
DOI: 10.1152/ajpcell.00013.2010
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxic preconditioning enhances bone marrow mesenchymal stem cell migration via Kv2.1 channel and FAK activation

Abstract: Transplantation using stem cells including bone marrow mesenchymal stem cells (BMSCs) is emerging as a potential regenerative therapy after ischemic attacks in the heart and brain. The migration capability of transplanted cells is a critical cellular function for tissue repair. Based on our recent observations that hypoxic preconditioning (HP) has multiple benefits in improving stem cell therapy and that the potassium Kv2.1 channel acts as a promoter for focal adhesion kinase (FAK) activation and cell motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 55 publications
12
102
0
4
Order By: Relevance
“…Although previous studies have reported the hypoxic culture conditions for preconditioning of cell-based therapy [17][18][19], the optimal culture conditions remain unknown. In this study, Car9 and Vegf expression increased significantly in rMSCs under the 1% pO 2 hypoxic condition compared with that under the normoxic condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have reported the hypoxic culture conditions for preconditioning of cell-based therapy [17][18][19], the optimal culture conditions remain unknown. In this study, Car9 and Vegf expression increased significantly in rMSCs under the 1% pO 2 hypoxic condition compared with that under the normoxic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Culturing cells under hypoxic conditions is a less invasive, alternative method to pre-condition of transplanted cells [17][18][19]. Although MSCs are usually cultured under normoxic conditions, MSCs exist in low oxygen (hypoxic) conditions in vivo [20] and the oxygen tensions are an important factor during MSC culture because stem cells are particularly sensitive to their microenvironment [21].…”
Section: Introductionmentioning
confidence: 99%
“…Pretreated or genetically modified BMSCs targeting the elevation of these factors showed increased cell viability and enhanced migration and homing capacity to lesion sites (21,24,48,50,53,69). BMSCs can stimulate endogenous neuronal differentiation and synaptic connection, thus improving neuronal activity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic conditions can significantly promote the formation of the FAK-Kv2.1 complex, increasing focal adhesion kinase (FAK) phosphorylation and upregulating CXCR4 in MSCs. All of these hypoxic effects reinforce the migration capacity and the homing of transplanted cells to the lesion sites [73]. Maijenburg et al [76] investigated the process of MSC migration and found that nuclear receptors Nur77 and Nurr1 showed the highest expression in migratory MSCs.…”
Section: Enhanced Migration and Homingmentioning
confidence: 99%
“…These factors have been shown to share the same trophic mechanisms that are essential for the roles of grafted SCs, which are necessary for their survival. Upregulated factors may include angiopoietin-I, VEGF, hepatocyte growth factor (HGF), placental growth factor (PlGF), BDNF, and fibroblast growth factor-2 (FGF-2) [65,72,73]. Treatment using some of these recombinant proteins or the induced endogenous expression of these proteins to enhance the secretion effects can reduce neuronal death and promote angiogenesis and attenuate many pathophysiological changes.…”
Section: Enhanced Secretion Effectsmentioning
confidence: 99%